The role of youtube in Malaysian university students’ media consumption: a focus on music and platform preferences - Heng, Amanda Yan Chwen (2024)

(untitled)
This research paper seeks to unveil the role of YouTube in the media consumption habits of Malaysian university students, mainly focusing on their music preferences and usage of the platform. Based on the university students’ responses and their preferences, this study utilizes SPSS-generated tables to elucidate the primary purposes of YouTube usage among students, factors influencing their preferences over other platforms and its impact on music listening behaviours. The basic design involves descriptive analysis of demographic factors, YouTube usage habits, music consumption habits, user attitudes, impact of YouTube and satisfaction levels. The results reveal that YouTube is the predominant platform for music among respondents, with frequent daily and weekly engagement. Different age groups show varied engagement levels. A positive correlation is found between the frequency of music consumption on YouTube and the algorithm’s effectiveness in understanding users' preferences. Furthermore, most respondents use the platform for music discovery, which significantly influences their purchasing decisions, like buying music or attending concerts of artists found on YouTube. Overall, the findings underscore YouTube's significance as a primary source of music consumption for Malaysian university students, strongly impacting their media consumption behaviours and the music industry.